They Have Never Changed: Accountants in Movies - Ani Wilujeng Suryani; Miftahul Jannah; Hazreel Hasmi (Jurnal Dinamika Akuntansi dan Bisnis)
The purpose of this study is to examine how accountants are portrayed in recent box office films. The samples for this study were movies registered in the Internet Movie Database and Film Indonesia. The study focuses on the accountant who appears in movies as a main character, side character, and/or cameo. Movies with accountant as the character and winning at least one award were chosen in this study. The semiotic analysis of movie data involved three steps: viewing the entire film, focusing on the accountants’ character scene in accordance with the description criteria, and interpreting the characters denotatively, connotatively, and mythically. The findings demonstrate that the stereotype of accountants shown in movies is consistent with societal preconceptions, such as being a man's occupation, having a bean counter, being introverted, and committing money theft. However, in some movies, accountants are portrayed positively. This negative depiction of accountants may cause students to be reluctant to choose accountants as their career choice. Thus, public accounting firms will encounter difficulties in recruiting and sustaining their businesses. Framed with the social representation theory, this study contributes to the accounting literature by focusing on the depiction of the accountant's character shown in the film by using semiotic analysis to investigate the depiction of accountants in films released since 2000.